2010
DOI: 10.1016/j.lungcan.2009.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for limited-stage small cell lung cancer: A study of 284 patients

Abstract: Combined modality therapy is the standard care for limited stage-small cell lung cancer (LS-SCLC) and has led to a significant improvement in patients' survival. This study sought to investigate and define the importance of prognostic effects of known and controversial factors especially the impact of smoking status and treatment strategies. A total of 284 patients with LS-SCLC diagnosed and prospectively followed from 1997 to 2008 at Mayo Clinic; their characteristics and survival outcome were assessed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 35 publications
2
58
1
1
Order By: Relevance
“…The results of 2 studies in limited-stage small-cell lung cancer subjects were conflicting, although even in a study that failed to demonstrate statistically significant improvement on overall survival, subjects who quit smoking experienced a survival benefit. 10 This is very important in a detrimental disease such as small-cell lung cancer. The most important finding in the study involving early-stage non-small-cell lung cancer subjects 9 is the stronger beneficial effect of smoking cessation on overall survival and recurrence-free survival in light smokers compared with heavy smokers and in women.…”
Section: Discussionmentioning
confidence: 99%
“…The results of 2 studies in limited-stage small-cell lung cancer subjects were conflicting, although even in a study that failed to demonstrate statistically significant improvement on overall survival, subjects who quit smoking experienced a survival benefit. 10 This is very important in a detrimental disease such as small-cell lung cancer. The most important finding in the study involving early-stage non-small-cell lung cancer subjects 9 is the stronger beneficial effect of smoking cessation on overall survival and recurrence-free survival in light smokers compared with heavy smokers and in women.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of smoking may be mediated through inflammation, oxidative tissue damage, or immune suppression that acts on cancer progression [9,11]. Smoking-induced activated macrophages may generate reactive oxygen species that promote angiogenesis, tumor invasion, and metastasis [9,13]. Tobacco exposure also can alter multiple immunologic functions, including the innate and adaptive immune system [9].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of smoking may be mediated through inflammation, oxidative tissue damage, or immune suppression that act on cancer progression [9,11]. Smoking-induced activated macrophages may generate reactive oxygen species that promote angiogenesis, tumor invasion, and metastasis [9,13]. Furthermore, smoking may increase blood carboxy-hemoglobin, producing relative hypoxia [13], and hypoxia-inducible factor has been shown to contribute to the RCC tumorigenesis process [16].…”
Section: Introductionmentioning
confidence: 99%
“…For SCLC cases, smoking percentages for men and women were 98.5% and 90.8%, respectively (10). Another study revealed that those smoking at the time of diagnosis and continuing to do so had a higher mortality (11). 93.8 % of the cases in our study were smokers.…”
Section: Discussionmentioning
confidence: 47%